2016
DOI: 10.1161/circresaha.115.307202
|View full text |Cite
|
Sign up to set email alerts
|

Endocardium Contributes to Cardiac Fat

Abstract: Rationale: Unraveling the developmental origin of cardiac fat could offer important implications for the treatment of cardiovascular disease. The recent identification of the mesothelial source of epicardial fat tissues reveals a heterogeneous origin of adipocytes in the adult heart. However, the developmental origin of adipocytes inside the heart, namely intramyocardial adipocytes, remains largely unknown. Objective: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 46 publications
1
61
0
Order By: Relevance
“…A similar phenomenon of mesenchymal transformation and adipogenic differentiation of epicardial progenitors has been reported in the atrioventricular canal during embryonic development (11,40). Of note, the endocardium has been shown to contribute to cardiac adipocytes during development, but adult endocardial-to-fat transition has not yet been reported (41).…”
Section: Discussionsupporting
confidence: 62%
“…A similar phenomenon of mesenchymal transformation and adipogenic differentiation of epicardial progenitors has been reported in the atrioventricular canal during embryonic development (11,40). Of note, the endocardium has been shown to contribute to cardiac adipocytes during development, but adult endocardial-to-fat transition has not yet been reported (41).…”
Section: Discussionsupporting
confidence: 62%
“…Col1a2-CreER transgene (14), Tcf21-MerCreMer (24), PostnMerCreMer (6), Cdh5-CreER (27), Apln-CreER (28), Fabp4-CreER (29), R26R-tdTomato (16), R26R-rox-tdTomato (22), and R26R-GFP (46) mouse lines were previously described. Sox9-CreER was generated by homologous recombination using CRISPR/Cas9 methods (21).…”
Section: Methodsmentioning
confidence: 99%
“…Dre-rox recombination removes rox-flanked transcriptional stop cassette, resulting in permanent expression of tdTomato and irreversible labeling of all descendants (20, 21) ( Figure 3B). We crossed Pdgfra-DreER to the R26R-rox-tdTomato reporter line (22) and treated adult Pdgfra-DreER R26R-rox-tdTomato mice with tamoxifen to induce PDGFRA + cell labeling. Flow cytometric analysis of isolated fibroblasts or endothelial cells showed that approximately 50% of PDGFRA + fibroblasts without a distinct population of PECAM + endothelial cells were tdTomato + ( Figure 3, C and D), suggesting that Pdgfra-DreER efficiently and specifically labeled fibroblasts, but not endothelial cells.…”
Section: Col1a2mentioning
confidence: 99%
“…Because we found that the caudal part of the endocardium is located in proximity to the foregut endoderm and liver bud at times of hepatic vessel formation, we investigated whether the endocardium forms liver vasculature in addition to coronary arteries. To lineage trace the developing endocardium, we first crossed Nfatc1-dre mice with the rox reporter line Rosa26-rox-STOP-rox-RFP (Rosa26-RSR-RFP) to generate Nfatc1-dre; Rosa26-RSR-RFP embryos 21 . Dre, like Cre, is a site-specific recombinase and targets rox sites for recombination; it has previously been used for lineage tracing [22][23][24] .…”
Section: Nfatc + Endocardial Cells Contribute To Liver Vasculaturementioning
confidence: 99%